PEMBERDAYAAN KEWIRAUSAHAAN IBU-IBU RUMAH TANGGA MELALUI PELATIHAN PEMBUATAN BERBAGAI OLAHAN PISANG DI KELURAHAN PANGGUNG LOR - Andhy Tri Adriyanto; Iwan Prasetyo; Titi Purbo Sari (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2020)
Kelurahan Panggung Lor Kelurahan is one of the kelurahan in the District of North Semarang in the City of Semarang, Central Java Province. In Kelurahan Panggung Lor there are still a small number of household businesses and there are still many housewives who have unproductive time, so this makes it one of the good potentials for developing household business entrepreneurs. Empowering housewives to improve the family economy in the Village of Panggung Lor, North Semarang District, Semarang City.Basically the aim of community service is to provide new ideas about entrepreneurship and motivate housewives to become entrepreneurs. The target to be achieved is the community to be creative and can make a variety of processed products made from bananas to be one of the products as an opportunity for entrepreneurship, so as to increase family income and be able to analyze the feasibility of entrepreneurship in making snacks.The method of carrying out community service activities is the provision of training and discussion regarding the process of making snacks. The results and outcomes targeted by devotion are training in making economically valuable products in the form of various kinds of snacks, so as to increase understanding and knowledge about entrepreneurship in making snacks and can improve the family economy.